The effect of athletic mental energy on wrestlers’ sports courage and attitudes toward wrestling - Ahmet İslam (Physical Education of Students)
Background and Study Aim: This study aimed to determine whether athletic mental energy played a mediating role between wrestlers’ sports courage and attitudes toward wrestling.